Traditional Chinese Medicine (TCM) and Allergic Diseases - Chan, Helen H. L.; Ng, Tzibun (Current allergy and asthma reports, 2020)
Purpose of Review This paper purports to review recent relevant publications on the efficacy of traditional Chinese medicine in treating allergic diseases, to illustrate the pertinent mechanisms of action of TCM, and to explore the possible role of TCM in the management of allergic diseases in the foreseeable future. As TCM embodies multiple treatment modalities, only the most popular two, namely CHM (Chinese herbal medicine) and acupuncture, were discussed. Publications, especially reviews involving randomized controlled trials (RCTs) on the use of TCM on allergic diseases, published up to June 2019 were reviewed and analyzed. Papers reporting the mechanisms of action of TCM in allergic diseases were also included. Other publications in Chinese were also discussed. Recent Findings A startling escalation in the incidence of allergic diseases in the last several decades has posed tremendous social and financial burdens on the community. Failing to locate a cure for these chronic diseases, patients have resorted to using alternative medications of which traditional Chinese medicine (TCM) is a popular one. Thus CHM has been extensively employed for treating allergic diseases. Some investigations have been conducted to ascertain the therapeutic efficacy of CHM for allergic diseases. Summary Although CHM has been widely deployed for treating allergic diseases, it appears from the published data that there is a dearth of conclusive evidence to establish the effectiveness of CHM for allergic diseases. It is recommended that more large- scale RCTs with prolonged durations be carried out to corroborate the efficacy of CHM for allergic diseases. On the other hand, there is ample evidence indicating that acupuncture is useful when administered alone in allergic rhinitis and asthma or when applied as an adjunct to conventional western therapy. Evidence of its utility in atopic eczema and urticaria is not definitive. It is recommended that acupuncture be integrated into the therapy of allergic rhinitis and asthma, and that CHM be used as an adjunct in the treatment of allergic diseases on an individual basis.